THE IONIZED GAS AROUND STARFORMING GALAXIES - Vasiliev, E. O.; Ryabova, M. V.; Shchekinov, Yu. A. (Одеські астрономічні публікації, 2013)
We consider the evolution of metal- enriched gas exposed to a superposition of time- dependent radiation field of a nearby starburt galaxy and nearly invariant (on timescales 100 Myr) ex- tragalactic ionization background. We study the evolution of ionic species (particularly those commonly observed in galactic circumference) depending on the galactic mass and star formation rate, and derive conditions for the highly ionized oxygen, OVI, to appear in extended galactic haloes in absorption or emission spectra. We have found that the maximum OVI fraction can reach ~ 0.4 — 0.6 under the action of both ionizing radiation field, which is typical in haloes of starforming galaxies, and the extragalactic background, the fraction remains high in a wide temperature range. We have shown that the OVI fraction is high enough that even for ~ 0.1Zʘ metallicity we can explain large OVI column densities (log[N(OVI), cm-2] ~ 14.5 — 15.3) observed in the haloes of starforming galaxies by Tumlinson et al. (2011). Thus, the requirements to the sources of oxygen supply into the extended haloes become reasonably conservative.